The Influence of the Merchandise Inventory Accounting Information System on Internal Control of Merchandise Inventory: Study at One of The Companies Operating in The Service Sector in Bandung - Agmy Dewi Purwanto; Bulan Tati Fitria; Djajun Juhara; Adam Ramdani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study aims to examine the extent to which the Merchandise Inventory Accounting Information System impacts the Internal Control of Merchandise Inventory. The variables examined in this study are the Accounting Information System as the independent variable and Internal Control as the dependent variable. The population for this study consisted of the inventory department of a company operating in the service sector in Bandung. A sample of 40 individuals was selected for the investigation. The research employed a descriptive-analytic approach and verification analysis, utilizing questionnaires for data collection. The data analysis application employs the Statistical Package for Social Science (SPSS) Version 25 for Windows. The research employed the Correlation Coefficient Test, Simple Linear Regression, Determination Coefficient, and Normality Test for analysis. The Pearson Product Moment Correlation calculation indicates a